2019
DOI: 10.3390/ijerph16101781
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Kinetic Analysis of Degradation of Atrazine by US/PMS

Abstract: The degradation effect, degradation mechanism, oxidation kinetics, and degradation products of Atrazine (ATZ) by Ultrasound/Peroxymonosulfate (US/PMS) in phosphate buffer (PB) under different conditions were studied. It turned out that the degradation rate of US/PMS to ATZ was 45.85% when the temperature of the reaction system, concentration of PMS, concentration of ATZ, ultrasonic intensity, and reaction time were 20 °C, 200 μmol/L, 1.25 μmol/L, 0.88 W/mL, and 60 min, respectively. Mechanism analysis showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The use of ultrasound radiation showed a high removal of organic carbon, although the results were shown to be lower than those of UV-A and UV-C radiation. These results are in agreement with the work of Lu et al [70], who observed a 71.4% atrazine degradation in the PMS/US system.…”
Section: Sr-aops Applied To a High Load Wwsupporting
confidence: 93%
“…The use of ultrasound radiation showed a high removal of organic carbon, although the results were shown to be lower than those of UV-A and UV-C radiation. These results are in agreement with the work of Lu et al [70], who observed a 71.4% atrazine degradation in the PMS/US system.…”
Section: Sr-aops Applied To a High Load Wwsupporting
confidence: 93%
“…As can be seen from Figure 7B, when the concentration of ethanol reached 5 mM, the degradation percentage was 89.34%, indicating that SO 4 − · played a greater role than ·OH. The generation mechanisms of ·OH and SO 4 · − are consistent with Equations 3–5 53–55 FeIII+HSO5FeII+normalH++SnormalO5 FeII+HSO5FeIII+OnormalH+SnormalO4 SnormalO4+normalH2OSO42+OH+normalH+ …”
Section: Resultssupporting
confidence: 69%
“…The generation mechanisms of ÁOH and SO 4 Á À are consistent with Equations 3-5. [53][54][55] Fe III…”
Section: Effective Active Species Of the Catalytic Systemmentioning
confidence: 99%
“…However, comparing to the PMS dosage of 3 mM, the degradation rate of tetracycline decreased to 66.2% at the PMS dosage of 4 mM, which means that an appropriate increase in PMS dosage can promote the generation of more and •OH, and the tetracycline degradation. However, an excessive amount of PMS bursts and •OH, generating and •HO 2 with lower oxidizing capacity , and the reaction proceeds as follows [23] : As a result, there is an ideal PMS dosage for tetracycline degradation using DFUS/PMS.
Fig.
…”
Section: Resultsmentioning
confidence: 99%